(untitled) (AYUSHDHARA, 2024)
Varicose ulcer is one of the most common venous disorders which occur as a complication of varicose vein. Venous insufficiency, venous reflux and venous hypertension not only result in dilation and tortuosity of the veins but are also responsible for both dermatological and vascular complication, resulting in the manifestation of varicose ulcer. It is a slow healing chronic recurrent ulcer accounting for almost 80% ulceration of lower extremities. A 50 years old man visited the OPD with complains of pain, swelling, discolouration and wound over the anterior aspect of the left leg above the ankle joint for 6 months. He had a history of varicose vein since 10 years. Six setting of Jalaukavacharan (leech therapy) along with internal administration of Shamana Aushadhi and external cleansing and dressing of ulcer have been done for a period of 1 and a half month. Gradual improvements of symptoms have been observed. The complete ulcer healing evidence has provided an interesting and encouraging result to the scholar and practitioner of this field. The Shamana Aushadhi like Mahamanjisthadi kwath, Kaishor Guggulu, Yastimadhu, Guduchi Sattva and Jalaukavacharan as Sastra karma have showed excellent Vrana Ropaka or ulcer healing effect in a long standing critical venous ulcer.